The System of Evaluation Principles for the Economic Effects of Earth Remote Sensing Data Application for Solution of the Problems in Various Economy Branches - BUTROVA, Elena V.; MEDENNIKOV, Victor I. (Journal of Environmental Management and Tourism, 2019)
In this paper, based on an analysis of the application of Earth Remote Sensing (ERS) technologies in various sectors of the economy, a system of principles for the evaluation of the economic effect caused by the application of ERS data common to all industries is considered. For this purpose, the experience of the development of informatization of various industries in terms of integration technologies is analyzed.